2017
DOI: 10.5194/dwes-10-99-2017
|View full text |Cite
|
Sign up to set email alerts
|

Modeling particle transport and discoloration risk in drinking water distribution networks

Abstract: Abstract. Discoloration of drinking water is a worldwide phenomenon caused by accumulation and subsequent remobilization of particulate matter in drinking water distribution systems (DWDSs). It contributes a substantial fraction of customer complaints to water utilities. Accurate discoloration risk predictions could improve system operation by allowing for more effective programs on cleaning and prevention actions and field measurements, but are challenged by incomplete understanding on the origins and propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Husband et al [6,23] showed with laboratory experiments and on-site studies that increasing shear stress results in the mobilization of different cohesive layers of accumulated material in the pipes, mobilizing particles from different sizes and composition. The particle behavior can vary between DWDSs with different water quality and pipe materials, as shown by van Summeren and Blokker [7] with a modelling study based on sediment collected in the United Kingdom, in the Netherlands, and in Australia with different particle sizes and densities. Even within the same DWDS supplying water from a single water source, the composition of deposits or suspended particles can vary as a result of microbial activity [24] or inorganic composition (e.g., as a result of corrosion) [22].…”
Section: Impact Of Hydraulic Conditions On Particle Deposition and Re-suspensionmentioning
confidence: 91%
See 1 more Smart Citation
“…Husband et al [6,23] showed with laboratory experiments and on-site studies that increasing shear stress results in the mobilization of different cohesive layers of accumulated material in the pipes, mobilizing particles from different sizes and composition. The particle behavior can vary between DWDSs with different water quality and pipe materials, as shown by van Summeren and Blokker [7] with a modelling study based on sediment collected in the United Kingdom, in the Netherlands, and in Australia with different particle sizes and densities. Even within the same DWDS supplying water from a single water source, the composition of deposits or suspended particles can vary as a result of microbial activity [24] or inorganic composition (e.g., as a result of corrosion) [22].…”
Section: Impact Of Hydraulic Conditions On Particle Deposition and Re-suspensionmentioning
confidence: 91%
“…The complex hydraulic conditions resulting from the system configuration and varying water consumption have a direct impact on water quality. Turbidity, for example, is directly influenced by flow velocity variations impacting particle deposition and resuspension, as well as shear stress on pipe walls [4,6,7]. The impact of varying flow velocities on microbial parameters in the drinking water is, however, less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Central to their findings was the role of diurnal flow velocities on particle transport and fate. This connection between discolouration and hydrodynamic conditions has been supported by numerous experimental and theoretical studies; see van Summeren and Blokker (2017) and Armand et al (2018) for reviews on the topic. These studies have mainly focused on the development of predictive tools for modelling particle transport and accumulation processes.…”
Section: Introductionmentioning
confidence: 66%
“…Because such tools require extensive field testing and are generally limited to pipe-level assessments, their use in practice has not yet been widespread. Recognizing this limitation, van Summeren and Blokker (2017) presented a theoretical particle transport model, combining the effects of gravitational settling, hydraulic shear stresses, and bed-load transport. To complement this, several laboratory-based experimental studies have emerged to better understand the complex interactions between particle properties and pipe hydraulics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Dutch households are relatively water efficient compared to other industrialised countries [61]. More recently, however, the frequency and length of heatwaves have substantially increased, leading to environmental degradation [62], lower pressure, sometimes discolouration at the tap [63,64], and freshwater resources-particularly groundwater resources-are under pressure [65],. These developments are paving the way for the smallscale introduction of DWM as a means to enhance domestic water conservation.…”
Section: Methodsmentioning
confidence: 99%